Radiated tumor cell-derived microparticles effectively kill stem-like tumor cells by increasing reactive oxygen species - Hu, Yan; Wan, Chao; Yang, Xiao; Tian, Yu; Deng, Suke; An, Dandan; Wang, Yijun; Wang, Jiacheng; Liao, Zhiyun; Meng, Jingshu; Qin, You; Sun, Yajie; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Stem-like tumour cells (SLTCs) are thought to be the cellular entity responsible for clinical recurrence and subsequent metastasis. Inhibiting or killing SLTCs can effectively reduce recurrence and metastasis, yet little has been done to clear SLTCs because they are usually resistant to chemotherapy, radiotherapy, and even immunotherapy. In this study, we established SLTCs by low-serum culture and confirmed that the low-serum-cultured tumour cells were in a quiescent state and resistant to chemotherapy, showing features of SLTCs, consistent with the reported data. We demonstrated that SLTCs had high levels of reactive oxygen species (ROS). Based on the finding that radiated tumour cell-derived microparticles (RT-MPs) contained ROS, we used RT-MPs to kill SLTCs. We found that RT-MPs could further increase ROS levels and kill SLTCs in vivo and in vitro partially by ROS carried by the RT-MPs themselves, providing a new method for eliminating SLTCs.